Предмет: Алгебра,
автор: lada12354
(х-2)^2-х(х-4) и вот это а^2+1-2(3а-4)
Как решить?
8 класс
Ответы
Автор ответа:
0
х^2-4x+4-x^2+4x=4
a^2+1-6a+8=a^2-6a+9=(a-3)^2
a^2+1-6a+8=a^2-6a+9=(a-3)^2
Автор ответа:
0
какое неравенство доказать?
Автор ответа:
0
Спасибо большое)
Там я уже сама)
/Оказалось знаки перепутала, вот и не получалось)
Там я уже сама)
/Оказалось знаки перепутала, вот и не получалось)
Похожие вопросы
Предмет: Математика,
автор: alinaAndryan777
Предмет: Алгебра,
автор: andrirocity
Предмет: История,
автор: universam6175225
Предмет: Физика,
автор: struk
Предмет: Информатика,
автор: Adviles